Supercurrent in Graphene Josephson Junctions with Narrow Trenches in the Quantum Hall Regime. (28th May 2018) - Seredinski, Andrew; Draelos, Anne; Wei, Ming-Tso; Ke, Chung-Ting; Fleming, Tate; Mehta, Yash; Mancil, Ethan; Li, Hengming; Taniguchi, Takashi; Watanabe, Kenji; Tarucha, Seigo; Yamamoto, Michihisa; et al.
ABSTRACT: Coupling superconductors to quantum Hall edge states is the subject of intense investigation as part of the ongoing search for non-abelian excitations. Our group has previously observed supercurrents of hundreds of picoamperes in graphene Josephson junctions in the quantum Hall regime. One of the explanations of this phenomenon involves the coupling of an electron edge state on one side of the junction to a hole edge state on the opposite side. In our previous samples, these states are separated by several microns. Here, a narrow trench perpendicular to the contacts creates counterpropagating quantum Hall edge channels tens of nanometres from each other. Transport measurements demonstrate a change in the low-field Fraunhofer interference pattern for trench devices and show a supercurrent in both trench and reference junctions in the quantum Hall regime. The trench junctions show no enhancement of quantum Hall supercurrent and an unexpected supercurrent periodicity with applied field, suggesting the need for further optimization of device parameters.